Pollen analyses for pollination research, acetolysis - Jones, Gretchen D. (Journal of Pollination Ecology, 2014)
Analysis of the pollen associated with pollinators can reveal their role in pollination, the habitats and plants they visit, from where they migrated, what they eat, and dispersal patterns in and around cropping systems. However, finding pollen on and or in a pollinator depends on the technique used to recover the pollen. Acetolysis can be used to recover pollen from internal insect tissues (gut, alimentary canal, crop, etc.), external tissues (proboscis, legs, eyes, etc.) or both.Acetolysis is the best technique for recovering pollen because any tissue is dissolved and lipids and debris are removed from the sample and the pollen grains.This makes the diagnostic characteristics of the pollen grains more visible so that accurate pollen identification can be made.By using the proper technique, better pollen recovery can be made and thus better data can be obtained.